2018
DOI: 10.1080/10773525.2018.1507291
|View full text |Cite
|
Sign up to set email alerts
|

Resurgent lead poisoning and renewed public attention towards environmental social justice issues: A review of current efforts and call to revitalize primary and secondary lead poisoning prevention for pregnant women, lactating mothers, and children within the U.S.

Abstract: The recent Colorado Gold King Mine waste-water spill and Michigan's water supply re-routing program catastrophe, has directed renewed public attention towards resurgent environmental lead contamination threats. Leaded environments present social justice issues for children and mothers possessing blood lead levels (BLLs) > 5 μg/dL. Childhood lead exposure remains a continual U.S. public health problem manifesting in lifelong adverse neuropsychological consequences. The 2007 Inspector General Report demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 39 publications
(71 reference statements)
2
19
0
Order By: Relevance
“…Although it is more costly than targeted screening, universal BLL testing during early childhood would close gaps in identification by detecting all cases that are EBLL-positive [99]. Universal testing of early childhood BLLs would also allow for a near-complete understanding of the remaining troubled areas of Pb contamination, continuing socio-economic or racial/ethnic disparity, and how to devise better performing targeting, preventive, intervention, and abatement or remediation efforts [100,101]. Furthermore, conservative estimates demonstrate that each $1 US dollar invested in controls just for leaded paint hazards alone generate a return of at least $17 USD, which then results in a net savings of $181 billion USD [102].…”
Section: Targeted Screening and Public Health Implicationsmentioning
confidence: 99%
“…Although it is more costly than targeted screening, universal BLL testing during early childhood would close gaps in identification by detecting all cases that are EBLL-positive [99]. Universal testing of early childhood BLLs would also allow for a near-complete understanding of the remaining troubled areas of Pb contamination, continuing socio-economic or racial/ethnic disparity, and how to devise better performing targeting, preventive, intervention, and abatement or remediation efforts [100,101]. Furthermore, conservative estimates demonstrate that each $1 US dollar invested in controls just for leaded paint hazards alone generate a return of at least $17 USD, which then results in a net savings of $181 billion USD [102].…”
Section: Targeted Screening and Public Health Implicationsmentioning
confidence: 99%
“…19 Another study showed that 50% or fewer children in New York, New Jersey, Pennsylvania, and Michigan were screened for BLLs before 6 years of age, and Pennsylvania children had the lowest screening rate and the highest burden of EBLLs. 20 Only a few studies have examined independent effects of selected characteristics such as age, race/ethnicity, parental educational attainment, Medicaid enrollment, and neighborhood characteristics on the likelihood of receipt of lead testing. 10 , 11 It is unclear whether community-level characteristics interact with individual risk factors on the likelihood of being tested for BLLs.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, public health policy implemented in the late 1970s to remove Pb 2+ from paint and gasoline was effective in markedly reducing the overall levels of Pb 2+ in blood of the general population and in particular in children (Lanphear et al, 2003;Pirkle et al, 1994;Pirkle et al, 1998). However, there is still a significant number of children with blood Pb 2+ levels that are detrimental to their health (Christensen et al, 2019;Han et al, 2018;Neuwirth, 2018;Tirima et al, 2018). Recent events indicate that a significant number of municipalities suffer from Pb 2+ contamination in drinking water in homes and schools throughout the United States (Hanna-Attisha et al, 2016).…”
Section: Introductionmentioning
confidence: 99%